Indians of the Plains - Andrews, Elaine K (New York : Facts on File, 1992)
Examines the history, culture, changing fortunes, and current situation of the various Indian peoples of the Great Plains region
Includes index
Keywords: Indians of North America -- Great Plains -- Juvenile literature